Jessica's secret love - William, Kate.; Pascal, Francine (New York : Bantam, 1994)
Jessica falls blissfully in love with Jeremy but soon discovers that he is engaged to her good friend Sue.
6.3
5-8.
5-8
Keywords: Friendship -- Fiction; Love -- Fiction; Friendship -- Fiction; Love stories